3-Chloro-1, 2-propanediol (3-MCPD), 2-chloro-1, 3-propanediol (2-MCPD) and glycidyl esters in infant formula: a review. (December 2019) - MacMahon, Shaun; Beekman, Jessica
Highlights: Background on process-induced contaminants MCPD and glycidyl fatty acid esters in foods. Review of methodology for the detection of these contaminants in infant formula. Results of surveys for MCPD and glycidyl esters in infant formula, as well as exposure estimates. Abstract : Methods and survey results for the detection of monochloropropanediol (MCPD) esters and glycidyl esters in infant formula will be reviewed. These process-induced contaminants have been shown to be potentially carcinogenic and/or genotoxic, making their occurrence in foods a potential concern. The presence of MCPD and glycidyl esters in infant formula is of specific concern, due to infants' low bodyweights and the potential that infant formula is the sole source of nutrition. Methods employing various approaches for the extraction and detection of these contaminants in infant formula will be reviewed, as will the results of occurrence studies and exposure estimates that have been conducted around the world.